Molecular characterization of a soybean FT homologue, GmFT7 - Senhao Zhang (Nature Portfolio, 2021)
Abstract Soybean (Glycine max) is a vital oilseed legume crop that provides protein and oil for humans and feedstock for animals. Flowering is a prerequisite for seed production. Floral transition, from vegetative to reproductive stage, in a plant, is regulated by environmental (light, temperature) and endogenous factors. In Arabidopsis, Flowering Locus T (FT) protein is shown to be a mobile signal that moves from leaf to shoot apical meristem to induce flowering. However, FTs role in soybean is not fully resolved due to the presence of multiple (ten) homologs in the genome. Two of the ten FT homologs (GmFT2a and GmFT5a) have a role in the floral transition while GmFT1a and GmFT4 suppress soybean flowering. Recent deep sequencing data revealed that six FT homologs are expressed in shoot apical meristem and leaves during floral transition. One FT homolog, GmFT7 showed strong expression during soybean floral transition. Though bioinformatic analyses revealed that GmFT7 had high similarity with GmFT2a, ectopic GmFT7 expression in Arabidopsis could not promote flowering or rescue the late-flowering phenotype of Arabidopsis ft-10 mutant.